“Não tem jeito melhor de realizar as atividades de espanhol”: a criação, implementação e análise de uma WebQuest(WQ) para o ensino e a aprendizagem de língua espanhola no ensino médio. - Zilli, Bruno Ramires (2022)
The WebQuest (WQ) consists of an investigative methodology, in which the objective is to transform information gathered on the internet into knowledge, through tasks to be performed. The methodology emerged in 1995, in a training course given by Professor Bernie Dodge, from the University of San Diego, and, since then, many studies in the most diverse areas of knowledge began to gain strength and, in the teaching of Languages, it was not different. Therefore, the present work aimed to create, implement and analyze a WQ for the teaching and learning of Spanish as an Additional Language in the context of Basic Education and presents the results of the research developed in the Graduate Program in Educational Technologies in Network (PPGTER), research line for the Development of Educational Technologies in Network (LP1), at the Federal University of Santa Maria (UFSM). For this, a qualitative research was carried out, with quantitative elements, in a 3rd year high school class, in a public school on the outskirts of Santana do Livramento - RS, based on the theoretical assumptions of action research (TRIPP, 2015). As instruments for data collection, the following were used: a) socioeconomic questionnaire; b) field notes and; c) Post-WQ questionnaire. In addition, to support the present research, the WQ conception of Dodge (1995) and Barato (2004) was used, in addition to studies on the teaching and learning of Languages mediated by the New Digital Technologies of Information and Communication (NTDICs) of Moran (2017), Paiva (2018) and Leffa (2020), as well as the ideas of the Project Pedagogy (PP) of Leite (2008) and the Social Interactionist Theory of Vygotsky (1970), for the creation of the WQ. For the analysis of the results, Bardin's Content Analysis (1977) was chosen and, from this analysis, it can be observed that the methodology contributed significantly in the classes in which it was used, not only promoting engagement on the part of the students, but also the learning of the language, as well as discussions pertinent to the subject worked. In addition, with the creation of WQ Las profesiones as a pedagogical product, which requires a professional master's degree, I hope to be able to contribute with other Spanish Language teachers when carrying out an activity using the methodology.